Asparagus cochinchinensis: A review of its botany, traditional uses, phytochemistry, pharmacology, and applications - Wang, Meng; Wang, Shuang; Hu, Wenjing; Wang, Zhibin; Yang, Bingyou; Kuang, Haixue (Frontiers in Pharmacology, 2022)
Asparagus cochinchinensis (Lour.) Merr. (A. cochinchinensis) is a traditional herbal medicine that is used to treat constipation, fever, pneumonia, stomachache, tracheitis, rhinitis, cataract, acne, urticaria. More than 90 compounds have been identified from different structural types in A. cochinchinensis, including steroidal saponins, C21-steroides, lignans, polysaccharides, amino acids, etc. These bioactive ingredients make A. cochinchinensis remarkable for its pharmacological effects on anti-asthma, anti-inflammatory, anti-oxidation, anti-tumor, improving Alzheimer’s disease, neuroprotection, gut health-promoting and so on. Moreover, A. cochinchinensis also plays an important role in food, health product, cosmetic, and other fields. This review focused on the research publications of A. cochinchinensis and aimed to summarize the advances in the botany, traditional uses, phytochemistry, pharmacology, and applications which will provide reference for the further studies and applications of A. cochinchinensis.